Use of 3-[18F]fluoropropanesulfonyl chloride as a prosthetic agent for the radiolabelling of amines: Investigation of precursor molecules, labelling conditions and enzymatic stability of the corresponding sulfonamides - Löser, Reik; Fischer, Steffen; Hiller, Achim; Köckerling, Martin; Funke, Uta; Maisonial, Aurélie; Brust, Peter; Steinbach, Jörg (Beilstein Journal of Organic Chemistry, 2013)
3-[18F]Fluoropropanesulfonyl chloride, a recently proposed prosthetic agent for fluorine-18 labelling, was prepared in a two-step radiosynthesis via 3-[18F]fluoropropyl thiocyanate as an intermediate. Two benzenesulfonate-based radiolabelling precursors were prepared by various routes. Comparing the reactivities of 3-thiocyanatopropyl nosylate and the corresponding tosylate towards [18F]fluoride the former proved to be superior accounting for labelling yields of up to 85%. Conditions for a reliable transformation of 3-[18F]fluoropropyl thiocyanate to the corresponding sulfonyl chloride with the potential for automation have been identified. The reaction of 3-[18F]fluoropropanesulfonyl chloride with eight different aliphatic and aromatic amines was investigated and the identity of the resulting 18F-labelled sulfonamides was confirmed chromatographically by comparison with their nonradioactive counterparts. Even for weakly nucleophilic amines such as 4-nitroaniline the desired radiolabelled sulfonamides were accessible in satisfactory yields owing to systematic variation of the reaction conditions. With respect to the application of the 18F-fluoropropansulfonyl group to the labelling of compounds relevant as imaging agents for positron emission tomography (PET), the stability of N-(4-fluorophenyl)-3-fluoropropanesulfonamide against degradation catalysed by carboxylesterase was investigated and compared to that of the analogous fluoroacetamide.
Keywords: fluorine-18; hydrolytic metabolism; prosthetic groups; radiochemistry; sulfonamides